2022
DOI: 10.18805/ag.r-2455
|View full text |Cite
|
Sign up to set email alerts
|

Kharif Onion Production in India- Present Status and Future Potential: A Review

Abstract: Onion is one of the most important commercial crops in India which is used as a vegetable, spice and rich in medicinal properties. In India major onion producing states are Maharashtra, Karnataka, Madhya Pradesh, Gujrat, Bihar, Andhra Pradesh and Rajasthan. In South India onion is cultivated three times in a year as rabi, kharif and late kharif crop whereas, in North India it is generally cultivated as rabi crop. Major portion (60%) of onion produce comes from rabi season while kharif and late kharif crops con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Although there was no significant difference (P >0.05) in yield in both stations, the Pink 1358 onion yield was lower compared to the Pune red at Lingmethang condition while there was no significant difference at Wengkhar condition. Similar results were also reported in the studies carried out on bulb onion varieties during the summer season in India (Sharma & Chauhan, 2022).…”
Section: Yieldsupporting
confidence: 90%
See 2 more Smart Citations
“…Although there was no significant difference (P >0.05) in yield in both stations, the Pink 1358 onion yield was lower compared to the Pune red at Lingmethang condition while there was no significant difference at Wengkhar condition. Similar results were also reported in the studies carried out on bulb onion varieties during the summer season in India (Sharma & Chauhan, 2022).…”
Section: Yieldsupporting
confidence: 90%
“…Other than the production season, good storage structures and additional varieties need to be explored that are suitable for both summer and winter productions which will give higher yield and has a good storage quality, so that the growers would have a choice of variety. Sharma & Chauhan, (2022) reported that the variety Agrifound Dark Red which is the popular and most cultivated variety in India is suitable for summer season production, and Khade, Gorrepati, & Thangasamy, (2017) reported that varieties such as Bhima Raj and Bhima Red can be grown in all the seasons. These varieties could be evaluated in the Bhutanese growing conditions to have a choice and suitable variety both for the summer and winter production of bulb onion in the country.…”
Section: Figure 1 Statistical Comparison Of the Yield Of Bulb Onion A...mentioning
confidence: 99%
See 1 more Smart Citation
“…India produced 26.64 million tonnes of onion bulbs from 1.62 million hectare area in the year 2021-2022 [5]. The onion production in India is divided into three crop seasons: Kharif (October to December), late Kharif (January to March) and Rabi (April to May) [6]. Stored Rabi onion is used for domestic and export markets from June to October, making it essential for regular supply.…”
Section: Introductionmentioning
confidence: 99%